Pelabuhan Boom Batu Jambi: Perjalanan Dari Pelabuhan Bersejarah Menuju Destinasi Komersial Moderen - Khasanah, Uswatun; Siregar, Isrina (FLORESIENSIS, 2025)
This article discusses the journey of Boom Batu Port in Jambi from a historical port to a modern commercial destination, focusing on the impact of the World Trade Center (WTC) mall construction, which led to the loss of part of this cultural heritage site. Using historical research methods and library-based data collection techniques, this study aims to uncover the role of Boom Batu Port in the social, economic, and cultural aspects of Jambi's community, as well as how modernization threatens the preservation of this historical site. Data were collected through a literature review, referencing historical documents, records, and other relevant literature. The findings reveal that although commercial development brings positive economic impacts, the loss of Boom Batu Port’s heritage value diminishes Jambi's historical significance and cultural identity. This study hopes to provide a critical perspective on the importance of balancing modernization with the preservation of historical heritage amid economic growth.